A Trial of Hyperimmune Globulin to Prevent Congenital Cytomegalovirus Infection. Issue 1 (January 2022) - Hughes, Brenna L.; Clifton, Rebecca G.; Rouse, Dwight J.; Saade, George R.; Dinsmoor, Mara J.; Reddy, Uma M.; Pass, Robert; Allard, Donna; Mallett, Gail; Fette, Lida M.; Gyamfi-Bannerman, Cynthia; Varner, Michael W.; et al.
Abstract : (Abstracted from N Engl J Med 2021;385:436–444) Congenital cytomegalovirus (CMV) infections are associated with stillbirth, neonatal death, deafness, and cognitive and motor delay. Small observational studies have evaluated CMV hyperimmune globulin to prevent congenital infection in women with primary CMV infection during pregnancy; however, the results were either inconsistent or inconclusive.